Volatomics-Assisted Characterization of Flavor Contributors During Ripening of Wallace Melon (Cucumis melo L.) - Yin, Hao; Jiang, Yongli; Zhong, Yu; Wang, Danfeng; Liu, Cong; Wang, Ji-Li-Te; Zhang, Minyan; Zhang, Chunrong; Deng, Yun (Current Nutrition & Food Science, 2024)
Background: Wallace melon has a powerful, pleasant aroma when ripe. However, little is understood about the aroma profile and the Volatile Organic Compounds (VOCs) biosynthesis during ripening. Objective: The aim of this study is to investigate the metabolome and transcriptome of Wallace melon to study the mechanism underlying its aroma formation systematically. Methods: HS-SPME/GC-MS and RNA-Seq were used to analyze the VOCs and associated genes of Wallace melon from three developmental stages (i.e., green, transition, and yellow stages). Results: The aroma profiles included 47 VOCs, which were in connection with 35 genes. Yellow- stage fruits are more aromatic than the melons in the transition and green stages, producing higher concentrations of total VOCs (2994.36 ng/g), with ethyl acetate (543.16 ng/g) being the most abundant compound. Transcriptomic analysis revealed that the biosynthesis of VOCs was mainly related to fatty acid and amino acid metabolisms. Moreover, the lipoxygenase-1 (MELO3C014482.2), alcohol dehydrogenase-2 (MELO3C017100.2), 3-ketoacyl-CoA synthase-3 (MELO3C010941.2), and hydroperoxide dehydratase (MELO3C018412.2) genes were closely related to alcohols/esters through correlation analysis. Conclusion: The information generated will deepen the understanding of Wallace melon storage quality and guide melon product development.
Keywords: GC-MS